(untitled) (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2023)
Vocational education and training (VET) is considered a master key towards socio- economic development. The main purpose of vocational education is to enhance the importance of education and develop the skill of students to make them more employable. The present research study is based on the awareness and interest of students in vocational education. The sample of the study is students from tribal populated districts of Madhya Pradesh. The methods which are applied in this study are random sampling methods by which data are collected through a structured questionnaire. Quantitative data are analyzed by using a statistical tool and some of the data are analyzed qualitatively according to the need of the objectives. The study revealed students are less aware of the term vocational education but they are interested to opt for some vocations to develop their skills and for their future livelihood.